Eschatology in Islamic Philosophy from the Perspective of Al-Ghazali - Ngatmin Abbas; Mukhlis Fathurrohman; Romadhon Romadhon (Yayasan Azhar Amanaa Yogyakarta, 2023)
This research aims to analyze Al-Ghazali's perspective on eschatology in Islamic teachings and the implications of his thoughts on the understanding and beliefs of Muslim individuals. The research methodology employed is literature analysis, examining Al-Ghazali's works related to eschatology and interpreting his views within the context of Islamic philosophy. The findings indicate that Al-Ghazali regards eschatology as an integral part of Islamic teachings that is crucial for preparing oneself to face the afterlife. Al-Ghazali emphasizes the importance of developing good morals, abstaining from sins, and maintaining a connection with God and fellow human beings. The implications of Al-Ghazali's perspective on the understanding and beliefs of Muslims are that the focus should primarily be on the hereafter while living in this world. Al-Ghazali's contribution in enriching the insights and understanding of eschatology from the perspective of Islamic philosophy includes the reinterpretation of eschatological concepts, the integration of philosophy and theology, and the development of profound philosophical reflections. This research demonstrates that Al-Ghazali's perspective on eschatology in Islamic teachings has significant implications for the understanding and beliefs of Muslims. Al-Ghazali's thoughts provide a valuable contribution in expanding the understanding of the afterlife and prioritizing the preparation for the hereafter. It offers a deeper comprehension of Al-Ghazali's views on eschatology and motivates Muslims to lead their lives in this world with a broader and responsible perspective.